2021
DOI: 10.1371/journal.pone.0258983
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognostic value of computed tomography-based attenuation correction on thallium-201 myocardial perfusion imaging: A cohort study

Abstract: Background Myocardial perfusion imaging (MPI) is a well-established diagnostic tool to evaluate coronary artery disease (CAD) and also an effective prognostic tool for patients with CAD. However, few studies investigated the prognostic value of attenuation correction (AC) in MPI, and the results were controversial. Objectives To investigate the prognostic value of computed tomography (CT)-based AC thallium-201 (Tl-201) MPI. Methods A total of 108 consecutive patients who underwent Tl-201 MPI and received c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(47 reference statements)
2
0
0
2
Order By: Relevance
“…All patients were further grouped by their SSS (a measure of ischemia severity). The Kaplan-Meier curve showed that the prognosis of the non-ischemia group was the best, and that of the severe ischemia group was the worst, similar to the results of previous studies ( 22 , 23 ), indicating that the prognosis of INOCA patients is affected by myocardial ischemia and that survival becomes increasingly poorer as ischemia becomes aggravated. Unexpectedly, the prognosis of patients with moderate ischemia was better than that of those with mild ischemia, possibly for the reason: after patients with SSS ≥ 4 were re-grouped, the SSS 9–13 group had the lowest number of patients and the least MACE, so it showed the best long-term prognosis on the survival curve.…”
Section: Discussionsupporting
confidence: 86%
“…All patients were further grouped by their SSS (a measure of ischemia severity). The Kaplan-Meier curve showed that the prognosis of the non-ischemia group was the best, and that of the severe ischemia group was the worst, similar to the results of previous studies ( 22 , 23 ), indicating that the prognosis of INOCA patients is affected by myocardial ischemia and that survival becomes increasingly poorer as ischemia becomes aggravated. Unexpectedly, the prognosis of patients with moderate ischemia was better than that of those with mild ischemia, possibly for the reason: after patients with SSS ≥ 4 were re-grouped, the SSS 9–13 group had the lowest number of patients and the least MACE, so it showed the best long-term prognosis on the survival curve.…”
Section: Discussionsupporting
confidence: 86%
“…All patients were further grouped by their SSS scores (a measure of ischemia severity). The Kaplan-Meier curve showed that the prognosis of the non-ischemia group was the best, and that of the severe ischemia group was the worst, similar to the results of previous studies [22,23], indicating that the prognosis of INOCA patients is affected by myocardial ischemia and that survival becomes increasingly poorer as ischemia becomes aggravated. Unexpectedly, the prognosis of patients with moderate ischemia was better than that of those with mild ischemia, possibly for the following reasons: after patients with SSS scores ≥ 4 were re-grouped, the sample sizes were greatly reduced; an important index of prognosis is recurrence of angina pectoris symptoms but evaluation is not objective, being largely based on subjective patient reports; and the SSS score is derived via manual semi-quantitative analysis and there is no signi cant difference between 8 and 9, although such patients belong to different groups.…”
Section: Analysis Of Prognostic Factorssupporting
confidence: 86%
“…2022;5(2):18-34. DOI: 10.37174/2587-7593-2022-5-2- [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] При подозрении на воспалительные реакции необходимо собрать полный анамнез пациента, провести его физикальный осмотр, направить на выполнение анализов (общий и биохимический анализ крови) и только после этого проводить инструментальное дообследование. Многие современные методы, такие как КТ, МРТ, УЗИ, часто не способны обнаружить воспаление до появления морфологических изменений в тканях, тогда как радионуклидные методы диагностики способны визуализировать очаг воспаления на ранних стадиях за счет локальных физикохимических изменений.…”
Section: рефератunclassified
“…Радиофармпрепараты на основе таллия аккумулируются преимущественно в тканях с интенсивным энергетическим обменом и могут использоваться для диагностики самых разнообразных опухолей, включая новообразования бронхов, лимфомы, рака щитовидной железы, костей и головного мозга, а также для перфузионной сцинтиграфии миокарда [21]. Изотопы таллия по своей природе близки к калию и способны проникать через клеточную мембрану с помощью натрий-калиевого ATФ-зависимого насоса и локализуются в митохондриях, являясь маркером целостности и работоспособности электрохимических цепей клетки [22]. Также радиоизотопы таллия могут использоваться для дифференциальной диагностики опухолевых и воспалительных процессов опорнодвигательного аппарата.…”
Section: остеотропные рфлп остеотропные рфлпunclassified